2022
DOI: 10.3390/dj10110211
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms and Dental Fluorosis: A Systematic Review

Abstract: Genetic factors contribute to susceptibility and resistance to fluoride exposure. The aim of this systematic review was to identify alleles/genotypes of single nucleotide polymorphisms (SNPs) associated with dental fluorosis (DF) and to identify them as protective or risk factors. PubMed, ScienceDirect, Cochrane Library, Scopus and Web of Science were searched for articles; the last search was performed in August 2022. Human studies that analyzed the relationship between SNPs and DF published in English were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Enrichment of metabolic pathways showed that curcumin is related to immune processes in caries, including the TNF signaling pathway and the AGE-RAGE axis. This cytokine has been reported to be increased in subjects with caries, and a polymorphism in this gene has also been associated with caries [ 29 , 30 ]. Similarly, RAGE mRNA levels have increased in the inflamed pulp of carious teeth [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of metabolic pathways showed that curcumin is related to immune processes in caries, including the TNF signaling pathway and the AGE-RAGE axis. This cytokine has been reported to be increased in subjects with caries, and a polymorphism in this gene has also been associated with caries [ 29 , 30 ]. Similarly, RAGE mRNA levels have increased in the inflamed pulp of carious teeth [ 31 ].…”
Section: Discussionmentioning
confidence: 99%